1980
DOI: 10.1007/bf02408519
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic dentinogenesis in the rabbit incisor: Circadian, ultradian, and infradian periods

Abstract: Summary.We have identified a variety of biological rhythms involved in the apposition and mineralization of dentin in the rabbit incisor.Animals were injected during the day or night with lead acetate at 2-week intervals--to provide biological time markers in forming dentin--and transverse undecalcified sections of the lower incisors were prepared for electron microprobe analysis. The positions of the lead markers were identified, and the continuous distribution of calcium and sulfur was measured at 1 /xm inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
(47 reference statements)
2
22
0
Order By: Relevance
“…Additional extra-short-period features between cross-striations, known as ultradian or intradian lines, have been described as fine bands that divide cross-striations into two or three segments (Gustafson and Gustafson, 1967;Dean, 1995;Dean and Scandrett, 1996;FitzGerald, 1996). There are currently no empirical data concerning the periodicity or causation of intradian lines in enamel, although there is evidence of an 8-12 h secretion rhythm in dentine (Rosenberg and Simmons, 1980;Ohtsuka and Shinoda, 1995). More detailed reviews of enamel microstructure may be found in Boyde (1989), Risnes (1998) and standard texts such as Aiello and Dean (1990), Hillson (1996), and Ten Cate (1998).…”
Section: Development Of Enamel Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Additional extra-short-period features between cross-striations, known as ultradian or intradian lines, have been described as fine bands that divide cross-striations into two or three segments (Gustafson and Gustafson, 1967;Dean, 1995;Dean and Scandrett, 1996;FitzGerald, 1996). There are currently no empirical data concerning the periodicity or causation of intradian lines in enamel, although there is evidence of an 8-12 h secretion rhythm in dentine (Rosenberg and Simmons, 1980;Ohtsuka and Shinoda, 1995). More detailed reviews of enamel microstructure may be found in Boyde (1989), Risnes (1998) and standard texts such as Aiello and Dean (1990), Hillson (1996), and Ten Cate (1998).…”
Section: Development Of Enamel Microstructurementioning
confidence: 99%
“…Experimental work on rat dentine by Rosenberg and Simmons (1980) and Ohtsuka and Shinoda (1995) demonstrated the presence of 2-3 intradian increments per day. FitzGerald (1996) reported a similar observation in human enamel, but his conclusions are difficult to verify without experimental evidence.…”
Section: Additional Short-period Featuresmentioning
confidence: 99%
“…Increments of enamel and dentin reflect systematical metabolic rhythms [11,21], and many studies have revealed circadian patterns and even subdaily (infradian or ultradian) patterns in various animals [e.g. 3,7,17,18,22]. This periodicity theoretically allows for estimation of age, even in days; incremental lines have been used to estimate day-age at death in some anthropological studies [1,4,5,9].…”
mentioning
confidence: 99%
“…There are some data on records of parturition. Okada and Mimura, as they are cited by Rosenberg and Simmons (1980), found that daily layers slightly stained with hematoxylin (less calcified) were formed in incisor dentine of rabbits just before parturition. The lightly stained bands were found in incisor dentine of 7 out of 9 lactating mice of genus Apodemus; their position in relation to the pulp cavity allowed them to be formed during parturition (Klevezal 1996).…”
Section: Discussionmentioning
confidence: 89%
“…Daily layers were found in incisors of many laboratory and wild mammals (see Klevezal 1996 for a review). Ultradian layers of unclear periodicity were also described for several cases (Rosenberg and Simmons 1980, Ohtsuka and Shinoda 1995. Records of some events of animal life connected directly or indirectly with body growth and mineral metabolism were found against the background of these daily and ultradian layers.…”
Section: Introductionmentioning
confidence: 93%